Influence of various antibacterial preparations on rate and efficiency of gain by young pigs - G L Allee; D A Schoneweis (Kansas Agricultural Experiment Station Research Reports, 1973)
Two trials involving 128 pigs were conducted to study the effects of antibacterial preparations on rate and efficiency of gain by young pigs. In both trials, the antibacterial preparations increased rate of gain. In trial I, there were no differences in performance of pigs fed ASP-250, Mecadox, or TNA-290. In the second trial, pigs fed Mecadox gained faster than pigs fed ASP-250, Furox or Neo-Terramycin. Pigs fed diets supplemented with the various antibacterial preparations utilized feed more efficiently than those fed the nonmedicated basal diet.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Antibacterial preparations; Rate of gain; Efficiency of gain